The concept of creating universal systems for the environmental certification of transport diesels based on mini- and microtunnels - Polivyanchuk, A. P. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2017)
Purpose. Creation of a scientific and practical basis for the development on the basis of mini and micro tunnels of universal low-cost systems for the environmental certification of transport diesel engines in terms of the mass emission of particulate matter with exhaust gases. Methods. Analysis and synthesis of information when studying the systems of ecological certification of diesel engines, physical and mathematical modeling, experimental research of working processes, technical characteristics and efficiency indicators of tunnels. Results. The technical characteristics of mini and micro-tunnels as control systems for mass emissions of diesel particulate matter are considered. The concept of the creation of universal mini- and microtunnels is proposed based on the principles of increasing their compactness, dynamism, management efficiency and accuracy. Conclusions. The results of theoretical and experimental researches and developments on increasing the universality of mini- and microtunnels are presented: mathematical models of work processes, resulting errors and performance indicators of tunnel; new isokinetic and compensation methods for controlling exhaust gas samples; prototypes of a minitunnule with an isokinetic sampler MT-1, microtunnels MKT-1 and MKT-2; test benches for studies of thermal processes in tunnels, isokinetic and compensation sampling regimes; results experimental development of certification procedures for measuring emissions of particulate matter from automotive, tractor and diesel locomotives.